Pemanfaatan Teknologi Informasi untuk Pengembangan Desa Wisata Widarapayung Wetan melalui Pemberdayaan Kelompok Sadar Wisata (Pokdarwis) - Linda Perdana Wanti; Fadillah; Annisa Romadloni; Ganjar Ndaru Ikhtiagung; Nur Wachid Adi Prasetya; Andesita Prihantara; Isa Bahroni; Ilham Aditya Pangestu (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2022)
Efforts to create a productive society and develop the world of tourism around their homes require attention from both the community and the government. Widarapayung Wetan Village in Cilacap Regency is a village that has tourism potential that has not been developed optimally. The problem in Widarapayung Wetan village related to tourism is that there is no quality, interesting, and informative tourism website that is used to promote the village's tourism potential. The development of superior aspects of the village requires appropriate and effective facilities and infrastructure to be used. A technological facility such as a tourist village website can help develop the potential of village tourism as well as be a means of promotion. The method of implementing this community service activity is training on the development and use of a tourist village website as a medium for introducing tourism potential by Pokdarwis in the village of Widarapayung Wetan. The expected output target is the development of village websites as a means of tourism promotion and increasing knowledge of tourism awareness groups (Pokdarwis) in managing tourism village websites.